Effect of Formation of van der Waals Complexes on Molecular Physical Properties. Issue 1 (1982) - Godzik, K.; Hays, T. R.; Henke, W. E.; Selzle, H. L.; Schlag, E. W.; Lin, S. H.
Abstract : Experimental data for anthracene-argon van der Waals complexes are presented as a function of bound argon atoms. The results are interpreted by a new theoretical model which is based on the Hartree-Fock method and can explain molecular physical properties in the transition region from isolated gaseous molecules to the condensed phase.